Re-evaluation of Petro physical Properties in Yammama Formation at Nasiriya Field - Jassim, Karrar Hayder; Al-Sudani, Jalal A. (Iraqi Journal of Chemical and Petroleum Engineering, 2019)
Nasiriya field is located about 38 Km to the north – west of Nasiriya city. Yammama, a giant lower cretaceous reservoir in Nasiriya field which is lithologically formed from limestone. Yammama mainly was divided into three main reservoir units YA, YB1, YB2 and YB3 and it is separated by impermeable layers of variable thickness. An accurate petro physical evolution of the reservoir is of great importance perform an excellent geological model so that four petro physical properties which are shale volume, porosity, water saturation and permeability was re-evaluated. The volume of shale was calculated using the density and neutron logs (VSH-DN) rather than using gamma ray log because of presence a uranium content in the formation that makes overestimation of shale volume. Cross plots of Density Neutron logs are used to determine porosity by using IP software, which is correcting automatically Density Neutron logs for the effect of shale. Indonesian equation was used to estimate water saturation for five wells rather than Archie equation in order to consider shale volume. Fuzzy logic was adopted to predict permeability instead of regression analysis (cross plot) because of presence of errors in the results in this method. The results are shown that units YB2 and YB3 have best reservoir quality.